The effects of doxapram on time to tracheal extubation and early recovery in young morbidly obese patients scheduled for bariatric surgery: A randomised controlled trial. Issue 6 (June 2020) - Fathi, Mohammad; Massoudi, Nilofar; Nooraee, Navid; Beheshti Monfared, Reza
Abstract : BACKGROUND: Bariatric surgery is a well established treatment of the obese. Postoperative respiratory failure and airway obstruction after bariatric surgery can often be attributed to the residual depressant effects of anaesthetics, sedatives and opioids. Peri-operative management of morbidly obese patients is still a concern for operating room professionals. OBJECTIVE: The evaluation of the effects of doxapram on the outcomes of general anaesthesia following bariatric surgical procedures in the morbidly obese. DESIGN: A single-blind randomised controlled trial with two parallel arms. SETTING: A tertiary care teaching hospital, Tehran, Iran, from 2017 to 2018. PARTICIPANTS: In total, 100 patients (69 women) with at least class two obesity were included in two groups of equal sizes and underwent bariatric surgery. MAIN OUTCOME MEASURES: The primary outcome was the time from the administration of doxapram to tracheal extubation. Secondary outcomes included vital signs and variables including peak expiratory flow rate, time to return to spontaneous breathing, time to eye-opening and hand-squeezing on the commands, and time to recovery. INTERVENTIONS: Both groups underwent general anaesthesia. The intervention group received a single dose of doxapram 1 mg kg −1 ideal body weight, immediately after reversal of neuromuscular blockade and after discontinuation of all anaesthetics. RESULTS: Doxapram decreased time to extubation, time to eye-opening and hand-squeezing, shortened recovery time and lowered end-tidal CO2 significantly (all P  < 0.001). Moreover, it increased peak expiratory flow rate, oxygen saturation, temperature, heart rate and blood pressure (all P  < 0.001). The two groups were similar in the bispectral index and mean arterial pressure (both P  > 0.05). None of our participants had complications attributable to doxapram. CONCLUSION: The postoperative use of doxapram improves peak expiratory flow rate, and decreases respiratory complications of anaesthesia during recovery in the morbidly obese undergoing bariatric surgery. Doxapram is well tolerated in young ASA physical status classes 1 to 2 morbidly obese patients; however, the anaesthesiologist should cautiously evaluate the vital signs for at least half an hour following the administration of doxapram. REGISTRATION: Iranian Registry of Clinical Trials (IRCT) http://www.irct.ir/ number IRCT2017060712203N9.